1997
DOI: 10.1093/bja/78.6.696
|View full text |Cite
|
Sign up to set email alerts
|

Use of inhaled nitric oxide in British intensive therapy units

Abstract: The use of inhaled nitric oxide in the critically ill has increased significantly over the past few years but little published information exists on standards for current practice. Sixty-four intensive therapy units in the UK were surveyed by questionnaire from which 54 (84.4%) satisfactory replies were received. We present the survey results and put forward recommendations based on current literature and our own clinical experience for the safe use of inhaled nitric oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The positive effect of inhaled NO on arterial oxygenation has probably been the most important reason for the widespread use [3] of INO in ARDS patients in Europe during the last years.…”
Section: Day 30mentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effect of inhaled NO on arterial oxygenation has probably been the most important reason for the widespread use [3] of INO in ARDS patients in Europe during the last years.…”
Section: Day 30mentioning
confidence: 99%
“…It also improves oxygenation and decreases pulmonary hypertension in patients with the acute respiratory distress syndrome (ARDS ) [2]. Numerous studies have confirmed these findings and INO is now often used in the treatment of patients with acute lung injury (ALI) and ARDS [3]. Despite its well documented physiological effects, it is important to evaluate whether INO is safe to use and whether it improves outcome in patients with ALI.…”
Section: Introductionmentioning
confidence: 99%
“…The current safety regulation for environmental NO gas is 25 ppm [1]. Moreover, NO also plays an important role in the physiological responses of our body.…”
Section: Introductionmentioning
confidence: 99%
“…It is also an important index in diagnosis of the chronic respiratory disease, asthma. However, its detection is rather difficult due to its extremely low concentration, which is about 20ppb [1,2]. The traditional method that was used to detect NO gas was based on measuring its variation of electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%